Patient acceptability of an ingestible sampling and imaging capsule (Samplecam) for bowel surveillance and early detection of colorectal cancer among Lynch Syndrome patients: a focus group study - Gil, Natalie M.; Merriel, Samuel W. D.; Sailem, Heba; Cummins, Gerard; Finn, Elena; Kerrison, Robert S. (Frontiers in Cancer Control and Society, 2025)
IntroductionLynch syndrome affects an estimated 1 in 279 people in the United Kingdom and presents a high lifetime risk of colorectal cancer. Current strategies to support early diagnosis among Lynch Syndrome patients include surveillance colonoscopy. Capsule endoscopy (CE), which enables visualization of the colon and rectum, is an ingestible imaging device, which could provide a potential means of enabling early detection between colonoscopies. However, current CEs are limited only to visual inspection and are unable to obtain samples from the colon, requiring follow-up colonoscopy for biopsy. To this end, we have been developing a novel ingestible device, which (1) can collect samples from the colon and (2) utilizes artificial intelligence to interpret images obtained (using images collected from colonoscopy and CE conducted with the same cohort). As with any new technology, perceived ease of use and usefulness will be key determinants of implementing ingestible devices within patient care. For this reason, we conducted a focus group study in which people living with Lynch Syndrome were invited to discuss their views on the device.MethodsOnline focus groups were conducted with adults (aged 18+ years) living with Lynch Syndrome. The focus groups aimed to explore their attitudes toward the use of a novel ingestible sampling and imaging device, for use within the surveillance pathway.ResultsThree focus groups, comprising 14 participants, were conducted. The majority of participants were of White British ethnicity (n = 13, 92.9%), female (n = 13, 92.9%) and aged 35 years or older (n = 10, 71.4%). We identified 11 barriers and five facilitators to the use of a novel ingestible device. Further, we identified six advantages, one disadvantage, and four potential indications for use. Attitudes were generally positive toward the device. However, participants were clearly opposed to the idea of this replacing colonoscopy entirely. The novel device was seen as something that could be implemented into the surveillance pathway to augment traditional methods and provide additional reassurance during long intervals between procedures.DiscussionResults were broadly consistent with previous findings that ingestible devices are perceived to be less invasive, less risky, and represent an alternative for people who fear the discomfort and embarrassment of colonoscopy. Previous studies have identified the need for further research with specific high-risk population groups, such as Lynch Syndrome patients. Our findings add to the literature by identifying several findings unique to these patients. Firstly, the recognition that a major barrier to ingestible device use is their inability to remove polyps, an important aspect of colonoscopy for Lynch Syndrome patients. Second, ingestible devices may also fail to recognize certain polyps common in Lynch Syndrome, such as those that are less pedunculated. Assurance around these issues will be required if implemented in the future.